Enhancing pH Modulation and Calcium Ions Release in External Resorption Artificial Defects - Azadeh Kheradyar; Mamak Adel; Majid Sirati-Sabet; Alireza Kolahdouzan; Sahar Shafagh (Wiley, 2024)
Conclusion: The Ca(OH)2, MTA, and CEM cement groups showed an increase in pH and the release of calcium ions at the external root resorption defects. Additionally, the application of ultrasonic energy increased the release of calcium ions at these sites.